Neuroprotective effects of gallic acid in a rat model of traumatic brain injury: behavioral, electrophysiological, and molecular studies - Mirshekar, Mohammad Ali (Iran J Basic Med Sci, 2018)
OBJECTIVE(S): Traumatic brain injury (TBI) is one of the main causes of intellectual and cognitive disabilities. Clinically, it is essential to limit the development of cognitive impairment after TBI. In the present study, the neuroprotective effects of gallic acid (GA) on neurological score, memory, long-term potentiation (LTP) from hippocampal dentate gyrus (hDG), brain lipid peroxidation and cytokines after TBI were evaluated. MATERIALS AND METHODS: Seventy-two adult male Wistar rats divided randomly into three groups with 24 in each: Veh + Sham, Veh + TBI and GA + TBI (GA; 100 mg/kg, PO for 7 days before TBI induction). Brain injury was made by Marmarou’s method. Briefly, a 200 g weight was fallen down from a 2 m height through a free-falling tube onto the head of anesthetized animal. RESULTS: Veterinary coma scores (VCS), memory and recorded hDG -LTP significantly reduced in Veh + TBI group at 1 and 24 hr after TBI when compared to Veh + Sham (P<0.001), respectively, while brain tissue content of interleukin-1β (IL-1β), IL-6, tumor necrosis factor-α (TNF-α) and malondialdehyde (MDA) were increased significantly (P<0.001). Pretreatment of TBI rats with GA improved clinical signs, memory and hDG-LTP significantly (P<0.001) compared to Veh + TBI group, while brain tissue content of IL-1β, IL-6, TNF-α and MDA were decreased significantly (P<0.001). CONCLUSION: Our results propose that GA has neuroprotective effect on memory and LTP impairment due to TBI through decrement of brain lipid peroxidation and cerebral pro-inflammatory cytokines.